Internalisasi Konsep Zuhud Berbasis QS. Al-Hadid:20 Dalam Fear of Missing Out (FoMO) Remaja Pengguna TikTok - Ahmad Khori; Bunga Ayu Lavenia; Wilda Solihat (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to examine the effectiveness of internalizing the concept of zuhud based on QS. Al-Hadid:20 in reducing Fear of Missing Out (FoMO) among teenage TikTok users at RW 06, Tanjungwangi Village, 2026. This research employs a quasi-experimental method with pre-test and post-test control group design. Subjects were 40 teenagers aged 13–18 years selected through purposive sampling, divided equally into experimental (n=20) and control (n=20) groups. The intervention consisted of four structured sessions integrating tafsir of QS. Al-Hadid:20 with zuhud value internalization activities. Data were collected using the adapted FoMO Scale (Przybylski et al., 2013; α=0.87) and analyzed using the Wilcoxon Signed-Rank Test and Mann-Whitney U Test. Results showed a statistically significant decrease in FoMO scores in the experimental group (Z=−3.92, p=0.001) with a mean reduction of 18.15 points, while the control group showed no significant change (p=0.432). These findings indicate that internalization of zuhud values derived from QS. Al-Hadid:20 is effective in reducing FoMO among teenagers who actively use TikTok.